PERAN INDONESIA DALAM KERJASAMA ASEAN-KOREA SELATAN MELALUI ASEAN-KOREA CENTRE - Windy Dermawan; Annisa Rohmaniah (Centre for Asian Social Science Research (CASSR), FISIP, UIN Bandung, 2019)
Cooperation between ASEAN and South Korea has been established since 1989. Until now, various kinds of cooperation have been implemented, one of which is the ASEAN-Korea Centre, an intergovernmental organization that aims to promote exchanges between South Korea and ASEAN member countries. Indonesia, as one of the member countries of ASEAN-Korea Centre, implements its foreign policy based on active and independent principle through the various role in supporting ASEAN-Korea Centre programs. This research is aimed to analyse the roles that Indonesia plays in the ASEAN-Korea Centre using the concept of national role conceptions from Holsti. The process of collecting and analyzing data is done by qualitative methods through the process of interviews, literature studies and content analysis. The result shows that Indonesia has a national role conception as a regional leader, active independent, and regional-subsystem collaborator in the ASEAN-Korea Centre. Indonesia's national role in the ASEAN-Korea Centre has strengthened Indonesia's international reputation and supported a variety of Indonesian diplomacy in ASEAN.